Urban-AODV: an improved AODV protocol for vehicular ad-hoc networks in urban environment - Mubarek, Foad Salem; Aliesawi, Salah A.; Alheeti, Khattab M. Ali; Alfahad, Nadia M. (International Journal of Engineering and Technology, 2018)
The Vehicular Ad-hoc Network or VANET is a special breed of Mobile Ad-hoc Networks (MANETs), which is used as a communication technology by the vehicles on roads to create a mobile network. VANETs have countless benefits and have tremendous potential to improve road safety, traffic efficiency, with added convenience and conform both for drivers and passengers on the road. From the architectural de-sign point of view, the communication is either Vehicle-to-Vehicle (V2V) or Vehicle-to-Infrastructure (V2I). Due to the dynamic nature of VANET, routing protocols in these networks have become an active area of research, posing various challenges and issues that need to be addressed. Most of the existing MANETs routing protocol need significant modifications to implemented them in the VANETs scenarios. For instance, Ad-Hoc on Demand Distance Vector (AODV) is one of the popular routing protocols that can be used in VANETs environment; however, it requires some enhancements in various aspects to make it suitable for VANETs communication paradigm. In this paper, we discuss these possible modifications, and propose various environmental parameters that when applied to AODV can make it more suit-able and compatible to be used in VANETs. We have proposed and implemented a new Route Discovery and Selection Phase to enhance the performance of the AODV protocol to make it usable by VANETs. The proposed modifications to AODV are implemented and tested specifically for the Urban Highway scenario. Therefore, our newly modified AODV protocol is known as Urban-AODV or U-AODV, as it fulfills the requirements in an Urban or city traffic scenario. We simulated U-AODV, and concluded that our proposed U-AODV reduces the average end-to-end delay, maximize packet delivery ratio and enhance link stability. Furthermore, it minimizes the communication over-head and routing control overhead of AODV in the urban/city traffic scenario.